Enhancing User Experience during Organizational Transformation: Effective Change Management and User Adoption Strategies - Yadav, Amit Kumar (Journal of Global Economy, Business and Finance, 2025)
Enterprises are undergoing transformation at a rate never seen before due to rapid technological innovation. According to research, up to 70% of change programs fail to meet their objectives because of inadequate user adoption strategies. This study looks into methods for enhancing user experience (UX) in transitional environments. It examines how businesses can optimize user adoption and minimize interruptions by streamlining transition processes, drawing from case studies and best practices. One important component that comes into play is effective change management, including proactive organizational shift responses and strategic planning. In order to maintain clarity and transparency during changes and to build stakeholder trust, communication is essential. Comprehensive training programs are also necessary to provide users with the information and abilities they need to operate new technologies. Through the integration of knowledge from various sectors and situations, this study emphasizes the significance of a comprehensive strategy for improving user experience in times of transition. It promotes approaches that priorities users' needs and preferences, facilitating easier changes and eventually enhancing organizational success and resilience.